Bakens, drumpels en webbe: (Hervormde) Teologie as kreatiewe onderneming - Staden, Piet van (HTS teologiese studies, 2013)
Beacons, thresholds and webs: Theology as creative endeavour. This article argues from the premise that theology is a creative undertaking. Nothing can be thought about God other than by thinking about people’s experience and understanding of God. Theology therefore speaks objectively about God from the subjective experience of God and from testimonies about that experience. Such reflections and testimonies are expressed in language. However, the inherent constraints of vocabulary and formulation render any linguistic expression of such spiritual encounters incomplete. Theology is always seeking for new possibilities of expression in order to overcome the constraints. It stands to reason that the figurative mode of expression will be preferred to the concrete or factual register of language because figurative language is more suited to articulate the elusive spiritual experience of meeting God through faith. Signposts, thresholds and webs are employed here as metaphors to emphasise the creative aspect of theology within the context of a changing world. They represent the three phases in the so-called rites of passage described by anthropologist Arnold van Gennep and refined by Victor Turner into an abstract model employed in the understanding of all similar experiences of ritual transference. Here the model is applied to the church and its theology.